Avaliação da imunidade inata uterina em vacas: transcrição endometrial de receptores de padrões moleculares microbianos no pós-parto e histopatologia após infusão de Escherichia coli inativada, na fase de estro - Telma da Mata Martins (2014)
Changes in the endometrial gene transcription of microbial molecular patterns receptors in the first postpartum week may result in susceptibility or resistance to uterine infections in taurine, zebu and crossbred cows. To test this hypothesis, 9 Holstein cows with retained placenta (RP) and 10 without RP were submitted to endometrial biopsies in the first and seventh postpartum days. The puerperium was monitored by gynecological exams. Following this study, the same procedures were applied in 9 Gir cows and 12 F1 Holstein x Gir cows without RP. All animals had endometrial transcription of TLRs 1/6, 2, 4, 5 and 9, NODs 1 and 2, and co-receptors CD14 and MD2. The transcriptions of TLR2, TLR4 and CD14 in Holstein cows with RP significantly reduced (P < 0.05) between the first and the seventh postpartum day. There was a higher transcription of TLR5 in Gir cows and lower transcription of TLR9 in F1 cows on the first postpartum day. The associations between puerperal occurrences and gene transcripts indicated that RP could interfere with endometrial immunity on the first postpartum day, increasing the transcription of CD14. Higher levels of transcription of CD14 were associated with uterine infections and delay of the involution process. In the last part of the study, 9 Zebu cows were inoculated by uterine infusion with PBS and 10 with suspension of inactivated E. coli, aiming to evaluate the endometrial inflammatory response. Neutrophilic infiltrates in 90% of samples of E. coli group at the stage of estrus characterized differing degrees of inflammation, suggesting that regulation of the immune response varies even within the same breed.